Tubulocystic Renal Cell Carcinoma of the Native Kidney in a Renal Transplant Recipient: A Rare Case Report - Brianna Ruch; Ashley J. Limkemann; Paulo Garcia; Cameron Benedict; Gaurav Gupta; Marlon Levy; Amit Sharma (Case Reports in Nephrology)
Tubulocystic renal cell carcinoma (TCC) is a rare and newly recognized variant of renal cell carcinoma, which may mimic benign cystic disease of the kidney. To our knowledge, we present the first reported case of a patient who, despite standard preoperative workup, developed TCC of his native kidney soon after receiving kidney transplantation. He was appropriately treated with native nephrectomy and has had no signs of reoccurrence 7 years postoperatively. Given the significant risk of malignancy in renal transplant patients, this case emphasizes the need for close monitoring of native cystic disease before and after transplantation, with low threshold to proceed with surgical intervention.